IL‐15 is a biomarker involved in the development of rapidly progressive interstitial lung disease complicated with polymyositis/dermatomyositis. (21st July 2020) - Shimizu, T.; Koga, T.; Furukawa, K.; Horai, Y.; Fujikawa, K.; Okada, A.; Okamoto, M.; Endo, Y.; Tsuji, S.; Takatani, A.; Umeda, M.; Fukui, S.; et al.
Abstract: Background: Polymyositis/dermatomyositis (PM/DM) is an autoimmune disease that is sometimes complicated with rapidly progressive interstitial lung disease (RPILD). However, serum and lung biomarkers that can predict RPILD development remain unclear. Objectives: To determine potential serum and lung biomarkers that can predict RPILD development in patients with PM/DM‐ILD. Methods: In total, 49 patients with PM/DM‐ILD were enrolled. We measured the serum levels of 41 cytokines/chemokines, ferritin and anti‐MDA5 antibody, compared them between the RPILD ( n  = 23) and non‐RPILD ( n  = 26) groups, and ranked them by their importance through random forest analysis. To distinguish the two groups, we determined biomarker combinations by logistic regression analysis. We also measured the bronchoalveolar lavage fluid (BALF) levels of 41 cytokines/chemokines. Using immunohistochemistry, we examined IL‐15 expression in lung tissues. The IL‐15 production was also investigated using A549 and BEAS‐2B cells. Results: The RPILD group had significantly higher IL‐15, IL‐1RA, IL‐6, CXCL10, VCAM‐1, anti‐MDA5 antibody and ferritin serum levels than the non‐RPILD group, but it had a significantly low CCL22 level. Meanwhile, anti‐MDA5 antibody, IL‐15, CXCL8, CCL22, IL‐1RA and ferritin were the best combination to distinguish the two groups. IL‐15 and CCL22 were also predictive marker for RPILD development in anti‐MDA5 antibody‐positive patients. Additionally, the RPILD group had significantly high IL‐15 levels in BALF. The lung tissues expressed IL‐15, which increased after cytokine stimulation in the A549 cells. Conclusion: This study identified a combination of biomarkers predicting PM/DM‐RPILD progression, and IL‐15 is an important cytokine for predicting RPILD development and reflecting ILD severity. Abstract :